Restaurant market in Kazakhstan: a portrait in comparison with the US market - Yerdavletova, Farida; Mukhambetov, Temirkhan (Business: Theory and Practice, 2014)
Market for restaurant services is one of the leading providers in terms of employment, scope of provided services and impact on the quality of life. At the same time, it remains as one of the closed and unexplored markets in terms of analysis of its problems and emerging trends. The aim of this article is a comprehensive analysis of industries in Kazakhstan by comparing it to the US market of restaurant industry. Furthermore, to improve management efficiency in restaurants, a research was conducted on behavioral differences of customers and level of management in restaurant industry, giving few recommendations on the use of management models.